The age of the corporate State versus the informational and cognitive public domain - Muela Meza, Zapopan Martín (Information for Social Change (UNITED KINGDOM), 2006)
This article analyses concepts of the bourgeois State, capitalist corporations and the democratic public domain. The main thesis presented is that today nation states have fused deeply with corporations; both orders have become transformed into one indivisible entity. The article considers how, in the Corporate State, society arrives at a dangerous condition; if the alternative forces to capitalism-imperialism are not able to oppose (under the rule of law) or dismantle its prime agent (the corporation/capitalistic companies), then humankind is in danger of having its democratic order hollowed-out or destroyed completely by the corporate State. Throughout the article, there is evidence of how the corporate State has corroded part of the public domain in the library sector by means of capitalistic commoditisation and privatisation of its services. Evidence exposes the corporationâs lack of ethics or morality. Finally, it is advocated that citizens re-establish the public domain and to force corporations under the rule of law to be judged by enforced legal accountability in a manner comparable to the relationship between the law and the public citizen.